Comparison of Broiler Performance in Closed House and Open House Systems in Trenggalek - Ana Rohmatul Laili; Ratna Damayanti; Boedi Setiawan; Sri Hidanah (Universitas Airlangga, 2022)
Background: According to the Indonesian Central Bureau of Statistics, broiler meat production in 2020 decreased by 6.3% from the previous year. Several factors can influence chicken productivity, one of which is cage management. The cage has a vital role in success because the comfort of the cage will result in maximum chicken productivity. Aim: To compare the productivity of broiler chickens reared using Closed House and Open House cage systems in the same partnership based on the value of Feed Conversion Ratio, Mortality, and Index Performance. Methods: Data collection was carried out using the literature and observative methods, namely direct observation on two farms using a Closed House and an Open House cage system in Trenggalek Regency in April 2021. Results: A FCR value of Closed House system cages has an FCR value of 1.416, whereas the Open House system was 1.605. The mortality of broiler chickens reared in the Open House system was 842, and in the closed house system was 572. The index performance of broiler chickens raised in the Closed House system was 366.5, whereas in an Open House system, the index performance was 319.4. Conclusion: The Feed Conversion Ratio (FCR), Mortality, and Index Performance Index (IP) value of broiler chickens reared in the Closed House system cage was higher than those in the Open House system cage.